Anthropocene genetic diversity loss in the marine tropics - René D. Clark; Brendan N. Reid; Eric Garcia; Marial Malabag; Robin S. Waples; Rene A. Abesamis; Jemelyn Grace P. Baldisimo; Abner A. Bucol; Kyra S. Fitz; Sharon F. Magnuson; Richard N. Muallil; Cleto L. Nanola; et al. (Proceedings of the National Academy of Sciences, 2025)
Genetic diversity is a crucial component of biodiversity, and as such, its maintenance and preservation is of high conservation concern. Tropical environments are undergoing intense rates of environmental change, and these changes may be driving large declines in genetic diversity. However, data on genetic diversity are highly skewed towards temperate regions. The degree to which diversity loss has occurred in tropical species, particularly marine species, remains an open and important question. Here, we directly compare genomic data from modern and museum collections of two commercially harvested nearshore marine fishes ( Equulites laterofenestra and Gazza minuta ) gathered from a single location in the Philippines, spanning a century of intense environmental change. These data reveal a marked loss in genetic diversity and evidence for multiple orders of magnitude reductions in effective population size ( N e ) in both species, indicating substantial genomic erosion. Such a decline highlights the long-lasting genomic consequences of anthropogenic activity and sheds light on an, until-now, invisible loss of diversity from the most biodiverse ocean region.